1993
DOI: 10.1164/ajrccm/148.4_pt_1.997
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of Rapid Serodiagnosis of Pulmonary Tuberculosis by ELISA with Cord Factor (Trehalose-6,6′-dimycolate) as Antigen Purified fromMycobacterium tuberculosis

Abstract: Immunoglobulin G (IgG) antibodies against purified cord factor (trehalose-6,6'-dimycolate) prepared from Mycobacterium tuberculosis H37Rv were determined by enzyme-linked immunosorbent assay (ELISA), and its diagnostic usefulness was evaluated. Serum specimens from 65 patients with active pulmonary tuberculosis, 58 patients with inactive pulmonary tuberculosis, 36 patients with diseases other than tuberculosis, and 66 healthy adults were examined. Patients with active pulmonary tuberculosis showed significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
45
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 7 publications
4
45
0
Order By: Relevance
“…Thus, no antigen tested would seem to be useful as a diagnostic tool in child TB patients. In the case of IgM detection in adults, these discouraging results (Table 2) have already been described for three of the four glycolipids (DAT, SL-I, and CF) (7,20) and for purified proteinaceous antigens (29).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Thus, no antigen tested would seem to be useful as a diagnostic tool in child TB patients. In the case of IgM detection in adults, these discouraging results (Table 2) have already been described for three of the four glycolipids (DAT, SL-I, and CF) (7,20) and for purified proteinaceous antigens (29).…”
Section: Discussionmentioning
confidence: 87%
“…They are 2,3-diacyltrehalose (DAT), 2,3,6-triacyltrehalose (TAT), 2,3,6,6Ј-tetraacyltrehalose 2Ј-sulfate (sulfolipid I [SL-I]), and trehalose-6,6Ј-dimycolate (cord factor [CF]). Using the enzyme-linked immunosorbent assay (ELISA) technique, several studies were performed with these antigens, and an extensive variability in immunoglobulin G (IgG) or IgM titers (6,7,11,18,20,(24)(25)(26) was obtained, i.e., test sensitivities were as different as 11 to 88% for the DAT antigen (11,25) and 51 to 93% for the TAT antigen (11,26). These contradictory results are due to the ELISA protocol used (the different antigen concentrations or the use of detergent in washing buffers) (15,30), or to the different sera groups analyzed (the number and type of patients and control subjects) (10).…”
mentioning
confidence: 99%
“…In addition to LAM, there are many glycolipids constituting the mycobacterial cell wall, such as trehalose 6,6-dimycolate (TDM). We used TDM, a glycolipid antigen purified from Mycobacterium tuberculosis H37Rv, in an enzyme-linked immunosorbent assay (ELISA) and reported that its sensitivity was 81% and its specificity was 96% (14). Subsequently, by combining TDM with more hydrophobic glycolipids, a new tuberculous glycolipid (TBGL) antigen was designed and a more sensitive serodiagnostic kit for TB, an anti-TBGL immunoglobulin G (IgG) test, was developed (11).…”
mentioning
confidence: 99%
“…Among all the haematological parameters, increased ESR has been observed to be a consistent finding in these cases [12,13]. Various other serological investigations, such as enzyme-linked immunosorbent assay (ELISA) for antibody to mycobacterial antigen-6 [14] and polymerase chain reaction (PCR) [15][16][17] have shown good sensitivity and specificity in diagnosing skeletal tuberculosis, but they are not useful for following the disease course or defining the end point of treatment. Even recent imaging modalities such as MRI cannot differentiate between residual infection and postinfection reparative process once treatment is completed [18,19].…”
Section: Discussionmentioning
confidence: 99%